Developing toughened aromatic polybenzoxazines using thermoplastic oligomers and telechelics, part 1: Preparation and characterization of the functionalized oligomers. Issue 19 (7th May 2014) - Hamerton, Ian; McNamara, Lisa T.; Howlin, Brendan J.; Smith, Paul A.; Cross, Paul; Ward, Steven
ABSTRACT The preparation and characterization of three families of thermoplastic oligomers (Mn = 2918–13263 g mol−1) based on polyarylsulfone (PSU) differing in both molecular weight and terminal functionality and one series of polyarylethersulfone (PES) of different molecular weights is reported. Infrared and nuclear magnetic resonance spectroscopy data support the formation of both the hydroxyl terminated oligomers and conversion (67–89% depending on molecular weight) to the telechelic PSU oligomer bearing reactive benzoxazine groups. Differential scanning calorimetry reveals that the onset of homopolymerization in the telechelic PSU oligomer occurs at around 100°C (peak maximum 125°C at 10 K/min) and rescans show values of the glass transition (for the homopolymers) ranging from 124 to 167°C depending on molecular weight. The influence on the oligomer backbone and terminal functionality is examined using thermal analysis. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40875.